2012
DOI: 10.5851/kosfa.2012.32.4.414
|View full text |Cite
|
Sign up to set email alerts
|

Meat Quality Traits of Longissimus Muscle of Hanwoo Steers as a Function of Interaction between Slaughter Endpoint and Chiller Ageing

Abstract: Carcass characteristics and meat quality traits as a function of endpoint months of slaughter age (26 vs 32 mon) and chiller ageing (1 vs 10 d) were evaluated for m. longissmus of 26 Hanwoo steers fed with commercial diets including whole crop barley silage. Totally twenty six Hanwoo steers for 6 mon of age that were fed until 26 mon of age constituted the short termfed group and fed until 32 mon of age constituted long-term fed group. Carcasses were chilled for 24 h and were graded. Strip loin samples were di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 70 publications
1
7
0
Order By: Relevance
“…In the present study, the effect of genotype and feed on fatty acid composition of intramuscular fat from LD muscle was restricted because the carcasses used in this study were de- rived from Hanwoo steers grown with commercial feed. The predominant fatty acids of intramuscular fat in the LD muscle from the 3 yield grades were palmitic (C16:0) and stearic (C18:0) acids as saturated fatty acids (SFA), oleic acid (C18:0) as a monounsaturated fatty acid (MUFA), and linoleic acid (C18:2) as a polyunsaturated fatty acid (PUFA), which agree with a report by Dashdorj et al (2012). Significant differences (p<0.05) in the contents of some fatty acids in intramuscular fat from LD muscle were confirmed among the 3 yield grades ( Table 5).…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…In the present study, the effect of genotype and feed on fatty acid composition of intramuscular fat from LD muscle was restricted because the carcasses used in this study were de- rived from Hanwoo steers grown with commercial feed. The predominant fatty acids of intramuscular fat in the LD muscle from the 3 yield grades were palmitic (C16:0) and stearic (C18:0) acids as saturated fatty acids (SFA), oleic acid (C18:0) as a monounsaturated fatty acid (MUFA), and linoleic acid (C18:2) as a polyunsaturated fatty acid (PUFA), which agree with a report by Dashdorj et al (2012). Significant differences (p<0.05) in the contents of some fatty acids in intramuscular fat from LD muscle were confirmed among the 3 yield grades ( Table 5).…”
Section: Resultssupporting
confidence: 90%
“…High intramuscular fat content in beef was reported to lead to high water holding capacity and low cooking loss, which make beef more juicy and tender (Jeremiah et al, 2003). Dashdorj et al (2012) reported that increasing the feeding duration of Hanwoo steers from 26 to 32 months resulted in increased intramuscular fat content and decreased cooking loss of Longissimus muscle, which led to increased juiciness, but they did not find a change in the tenderness of the Longissimus muscle. Park et al (2000) also re- ported increased scores for juiciness and tenderness with a gradual increase in the intramuscular fat content of LD muscle from Hanwoo cattle.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Even more, Hoving-Bolink et al [ 49 ] found higher meat tenderness in animals reared with maize silage than in those fed with grass silage. Texture, considered as WBSF, has a high variability, which is attributable to factors related to animals, environment, pre-slaughter or breed [ 16 ], sex [ 50 ], age at slaughter [ 51 ], slaughter weight [ 52 ], feeding system, feeding level [ 53 ], compensatory growth [ 54 ], average daily gain, physical activity or confinement time [ 55 ] as well as technological factors, maturation, packaging, temperature and cooking techniques.…”
Section: Resultsmentioning
confidence: 99%
“…From the results, we conclude that the intramuscular fat score at the 13 th rib can represent the fat content of loin when meat graders decide the grade of Hanwoo carcass. (Dashdorj et al, 2012;Jo et al, 2013;Jeremiah et al, 2003;Kim and Lee, 2003;Park et al, 2000). III.…”
mentioning
confidence: 99%